2016
DOI: 10.5604/12321966.1219182
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural injuries in Korea and errors in systems of safety

Abstract: It was found that most agricultural injuries were caused by a complex layer of root causes which were classified as errors in the systems of safety. This result indicates that not only training and personal protective equipment, but also regulation of safety design, mitigation devices, inspection/maintenance of workplaces, and other factors play an important role in preventing agricultural injuries. The identification of errors will help farmers to implement easily an effective prevention programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
1
12
0
1
Order By: Relevance
“…Therefore, further research is required to review a more diverse range of items on health and safety management, and include checklists developed by private organizations, such as agricultural and insurance companies, universities, and research institutions. Kim et al (2016) engaged in the analysis of causes of farmers' occupational injuries using the logic tree analysis, which confirmed that most safety incidents occur as a result of the accumulation of various errors in safety systems, rather than due to simple exposure to hazards or mistakes by workers [2]. However, the authors of the current study argue that the most optimal checklist for preventing farmers' occupational injuries should include the maximum number of items classifiable within the safety systems presented in this study.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…Therefore, further research is required to review a more diverse range of items on health and safety management, and include checklists developed by private organizations, such as agricultural and insurance companies, universities, and research institutions. Kim et al (2016) engaged in the analysis of causes of farmers' occupational injuries using the logic tree analysis, which confirmed that most safety incidents occur as a result of the accumulation of various errors in safety systems, rather than due to simple exposure to hazards or mistakes by workers [2]. However, the authors of the current study argue that the most optimal checklist for preventing farmers' occupational injuries should include the maximum number of items classifiable within the safety systems presented in this study.…”
Section: Discussionsupporting
confidence: 61%
“…According to previous studies, the occupational injuries faced by farmers are associated with farm management conditions and their socio-economic status [18,19]. Kim et al (2016) stated that farmers' occupational injuries occur due to errors in various safety systems, such as inefficient design of machines, lack of communication tools such as warning signs, and lack of training.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations